1998
DOI: 10.5172/conu.1998.7.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Learning with technology: Use of case-based physical and computer simulations in professional education

Abstract: This paper describes a multimedia technology project in midwifery education and how it is being developed to improve student learning experiences and outcomes. The role of the university providing quality education relevant to today's world and professional practice is emphasised. A collaborative (Royal Melbourne Institute of Technology and Australian Catholic University) interdisciplinary project 'Pregnancy Simulator: Developing and Enhancing Student Learning of Pregnancy Assessment Skills' was developed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…[2][3][4] A nursing study reported that the transfer of learning from case-based simulation to the "real world" was rapid. 5 Overall, computer-based case simulations have been documented to be successful educational tools in many healthcare professions including medicine, nursing, physical therapy, dentistry, and veterinary medicine. 2,3,[5][6][7][8][9][10] One study found that although computer-assisted learning was more efficient, its effectiveness was not superior to that of lecturebased education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] A nursing study reported that the transfer of learning from case-based simulation to the "real world" was rapid. 5 Overall, computer-based case simulations have been documented to be successful educational tools in many healthcare professions including medicine, nursing, physical therapy, dentistry, and veterinary medicine. 2,3,[5][6][7][8][9][10] One study found that although computer-assisted learning was more efficient, its effectiveness was not superior to that of lecturebased education.…”
Section: Discussionmentioning
confidence: 99%
“…5 Overall, computer-based case simulations have been documented to be successful educational tools in many healthcare professions including medicine, nursing, physical therapy, dentistry, and veterinary medicine. 2,3,[5][6][7][8][9][10] One study found that although computer-assisted learning was more efficient, its effectiveness was not superior to that of lecturebased education. 10 As with other healthcare professionals, the use of computers and the Internet has become a required skill for pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Performance feedback is often given in another room at a much later time, thus reducing learning opportunities for adaptive practice experience. (Lyons, Miller & Milton, 1998).…”
Section: Educational and Professional Issuesmentioning
confidence: 99%
“…The use of computer-based simulations as learning tools has been developed in many areas of health-care education: intensive care (Henry and Waltmire, 1992), child health (Lauri, 1992;Krawczak and Bersky, 1995), physical assessment (White, 1995), and midwifery (Woodsbn, 1997;Lyons, Miller and Milton, 1998). Clinical decision-making skills are another area where the value of simulation has been recognized.…”
Section: Simulationmentioning
confidence: 99%
“…This approach was taken in order to create a rich, effective multimedia learning tool, capable of developing deductive reasoning skills by giving individualized formative advice to the students. It is suggested that students learn most effectively with simulation when there is feedback immediately following an event (Johannson and Wertenberger, 1996;Lyons et al, 1998;Laurillard, 1995Laurillard, , 1997. In this way it is seen as relevant and becomes integrated into the learning experience.…”
Section: Simulationmentioning
confidence: 99%